A colônia imaginada : Anchieta e as metamorfoses do imaginário medieval na América portuguesa (1534-1597) - Alvim, Davis Moreira (2004)
The research presented hereinafter deals with Jesuit priest Jose de Anchieta"s (1534-1597) imaginary, by analyzing their medieval roots, as well as their metamorphoses in Portuguese America. Anchieta made use of medieval beastiaries, the demonology; directed earthly politics towards the spiritual world; believed he could count on heavenly support by means of hierophanies and chastisements; proclaimed the so-called fair war in God"s name for the conversion of the heathen; provided several people with a good death; wished for himself and called others to adhere to the ideal of martyrdom; defended the governor’s subordination to God and founded government authority on the power directly granted by the Deity. I have used as documentation some letters written by the Jesuit priest himself, comprising the period from 1554 to 1594, and the epic poem De Gestis Mendi de Saa, probably written within the period from 1560 to 1562 and published in Portugal by the first time in 1563. The main themes approached by the research were: the indian, the sacred, death, war, and tomism. Such themes have been set apart in an arbitrarian and didactic way during the explanation, but they surely intermingle and provide each other with sense, since Anchietan thought, as medieval thought likewise, would see no clear boundary between the purposes of politics and those of religion; would approach and deal with the worldly and the spiritual, by subordinating the former to the latter; would live and act on behalf of a sole, omnipresent, militarized God; and after all, would direct war, the government and the instant of death towards God.